MHD Jeffrey nanofluid past a stretching sheet with viscous dissipation effect - Zokri, S. M.; Arifin, N. S.; Salleh, Mohd Zuki; Mohd Kasim, Abdul Rahman; Mohammad, Nurul Farahain; Wan Yusoff, Wan Nur Syahidah (Institute of Physics Publishing, 2017)
This study investigates the influence of viscous dissipation on magnetohydrodynamic (MHD) flow of Jeffrey nanofluid over a stretching sheet with convective boundary conditions. The nonlinear partial differential equations are reduced into the nonlinear ordinary differential equations by utilizing the similarity transformation variables. The Runge-Kutta Fehlberg method is used to solve the problem numerically. The numerical solutions obtained are presented graphically for several dimensionless parameters such as Brownian motion, Lewis number and Eckert number on the specified temperature and concentration profiles. It is noted that the temperature profile is accelerated due to increasing values of Brownian motion parameter and Eckert number. In contrast, both the Brownian motion parameter and Lewis number have caused the deceleration in the concentration profiles.